Analisis Strategi Pemasaran Kinerja Usaha Serta Keberlanjutan Usaha Makanan Sweet Potato Creme di Kota Palembang - Aditya Prasetya; Joshua Rizkianto Gultom; Yulizar Kasih (MDP Student Conference, 2026)
This study aims to analyze the marketing strategy of business performance, potential, and feasibility of implementing the Sweet Potato Crème business as an innovative sweet potato-based dessert product in Palembang City. The scope of the study includes product analysis, marketing, operations, and business financial performance. The method used is a qualitative descriptive method with a business study approach, supported by primary data through a questionnaire survey of 41 respondents and secondary data from literature and business financial reports. The results of the study indicate that Sweet Potato Crème has a very high level of market acceptance, with consumer interest reaching 100%, supported by affordable prices, tastes that suit preferences, and effective online and offline marketing strategies. The conclusion of this study states that the Sweet Potato Crème business is feasible to be developed and has the potential to be sustainable as an innovative culinary product based on local food.